The effect of temperature and digested sewage sludge cover over tailings on the leaching of contaminants from Ballangen tailings deposit - Lu, Jinmei; Leiviska, Tiina; Walder, Ingar (Journal of Water and Climate Change, 2021)
Dry covers can be applied above tailings to reduce and prevent formation of acid mine drainage and leaching of contaminants. Efficiency of covers is affected by different parameters, of which temperature change under climate change context is one. Here, a laboratory column leaching experiment was performed under four temperatures, 5, 10, 14, and 18 °C on unoxidized tailings from Ballangen, Norway. 600 mL of water was added to each column every second week and leachate was collected and analyzed for pH, salinity, alkalinity, concentrations of sulfate, Co, Fe, Mn, Ni, and Zn. A thin layer of digested sewage sludge was added to columns after the 16th leaching cycle. In total, 21 leaching cycles were performed. Results showed low oxidation of tailings and therefore high pH and low salinity, SO42−, Fe, Ni, and Co in the leachates at leaching temperature of 5 °C. Addition of sludge cover slowed down oxidation of underlying tailings and decreased leaching of SO42−, Fe, Mn, Co, Ni, and Zn from the tailings deposit, especially at relatively high temperatures. 10 °C is a threshold temperature, below which leaching is not affected by the cover addition so much. At a leaching temperature higher than 10 °C, the sludge cover addition can reduce the leaching of elements significantly.